Physical activity and mental health status among elderly people - Benedetti, Tânia R Bertoldo; Borges, Lucélia Justino; Petroski, Edio Luiz; Gonçalves, Lúcia Hisako Takase (Revista de Saúde Pública, 2008)
OBJECTIVE: To evaluate the association between physical activity level and mental health status among elderly people. METHODS: This was a population-based survey with a probabilistic sample of 875 elderly people from a city of Southern Brazil, in 2002. The International Physical Activity Questionnaire and the Brazil Old Age Schedule questionnaire were applied. The mental health problems evaluated were depressions and dementia. Total physical activity (leisure-time, occupation, transportation and housework). After descriptive and bivariate analyses, adjusted analyses were performed by means of logistic regression, with adjustment for the factors of total physical activity, leisure-time activity and depression and dementia scores. RESULTS: There were statistically significant inverse associations between dementia and depression with total physical activity and leisure-time physical activity. The odds ratio for total physical activity adjusted for dementia among sedentary subjects in comparison with active subjects was 2.74 (95% CI: 1.85; 4.08), while the respective value adjusted for depression was 2.38 (95% CI: 1.70; 3.33). CONCLUSIONS: The results reinforce the importance of active lifestyles for preventing mental health problems among elderly people. It is inferred that the physical activity was able to reduce and/or delay the risks of dementia, although it cannot be stated that dementia is avoided through physical activity.